Bernard Herrmann - Music for the Movies - Waletzky, Joshua (naive vision, 2006)
Everybody's favorite Hollywood film composer, Bernard Herrmann, receives exceptionally intelligent treatment in this first-class analytical docu. Film scholar and casual fan alike will learn a great deal from this look at a man who professed disgruntlement with his work but turned out an inordinate number of great motion picture scores ... In a very tight hour, this film convincingly demonstrates why its subject was important, and reveals how an outstanding score can add immeasurably to the emotional and psychological impact of a picture. [www.variety.com]
Keywords: DVD-Video